Las salinas del mediodía alicantino a fines de la Edad Media - Hinojosa Montalvo, José (Investigaciones Geográficas, 1993)
Valencian salt, which during the Middle Ages was considered a royal prerogative, was principally found in the salt flats along the southern cost of Alicante, especially in the area known as La Mata. The leasing of the rights to exploit these flats was an important source of income for the Bailia of Orihuela, and the Santangel family was one of the most important leaseholders. The exportation of Valencian salt to Italian ports was clearly monopolized by the Genoese.